Algorithms of the protected information exchange in radio channels of a space navigation system - S. V. Shtanko; D. A. Lesnyk (Известия высших учебных заведений России: Радиоэлектроника, 2015)
To improve the security of information exchange throw navigation space system radio channels to prevent unauthorized use of the system is proposed to use high accuracy cryptographic methods to protect signal. This task allows to solve a cryptographic system that implements secure authentication protocols, key collection and information exchange.